Nucicla umbiliphora gen. et sp. nov.: a Quaternary peridinioid dinoflagellate cyst from the Antarctic margin. (2nd January 2019) - Hartman, Julian D.; Sangiorgi, Francesca; Bijl, Peter K.; Versteegh, Gerard J.M.
ABSTRACT: In the southern high latitudes, dinoflagellate cysts are an important microfossil group for both biostratigraphic and palaeoenvironmental interpretations purposes. In light of this, the peridinioid dinoflagellate cyst Nucicla umbiliphora gen. et sp. nov. from the Antarctic margin is formally described. Nucicla is dorsoventrally compressed, has a rounded pentagonal outline in dorso-ventral view, an epicyst that is only half as high as the hypocyst, an unusual archaeopyle formed by the loss of the three anterior intercalary plates, and a posterior sulcal plate that is positioned at the antapex. The species N. umbiliphora is characterised by a scabrate cyst wall and possesses undulated and/or crenulated folds/ridges. It has been so far exclusively found in Quaternary sediments obtained from the East Antarctic continental shelf and the Ross Sea. Although the dinoflagellate producing this cyst is as yet unknown, its brown color and the lack of autofluorescence suggest that the motile cell is likely a heterotrophic Protoperidinium species. As such, N. umbiliphora might benefit from the phytoplankton blooms occurring close to the Antarctic margin after seasonal sea-ice retreat.